2011
DOI: 10.1007/s11627-011-9367-2
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced production of tropane alkaloids in transgenic Scopolia parviflora hairy root cultures over-expressing putrescine N-methyl transferase (PMT) and hyoscyamine-6β-hydroxylase (H6H)

Abstract: Scopolia parviflora adventitious roots were metabolically engineered by co-expression of the two gene putrescine N-methyl transferase (PMT) and hyoscyamine-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Overexpression of PMT and H6H in Hyoscyamus niger and Atropa belladonna in transgenic hairy root cultures [65,66] and expressional analysis of H6H gene from Hyoscyamus niger and Hyoscyamus tenuicaulis [68] has been reported. Our study is also in agreement with the work carried out regarding the expressional analysis of PMT and H6H genes in Scopolia parviflora [67].…”
Section: Plos Onesupporting
confidence: 92%
See 1 more Smart Citation
“…Overexpression of PMT and H6H in Hyoscyamus niger and Atropa belladonna in transgenic hairy root cultures [65,66] and expressional analysis of H6H gene from Hyoscyamus niger and Hyoscyamus tenuicaulis [68] has been reported. Our study is also in agreement with the work carried out regarding the expressional analysis of PMT and H6H genes in Scopolia parviflora [67].…”
Section: Plos Onesupporting
confidence: 92%
“…and scopolamine concentrations in Hyoscyamus niger [65], Atropa belladonna [66], Scopolia parviflora [67]. Our study showed a maximum increase of 10.3 and 4.8 fold in the expression of H6H and PMT, respectively, at 0.03% EMS to control, suggesting that EMS at low concentration leads to an increase in expression, whereas the decrease in expression is seen with a higher concentration of EMS.…”
Section: Plos Onementioning
confidence: 43%
“…Combining the overexpression of both PMT and H6H in A. belladonna has resulted in approximately a 2.5-fold increase of scopolamine above wild-type levels (Liu et al, 2010). This growth increase could be attributed to the role of polyamines in the processes of growth and cell differentiation (Kang et al, 2011). Using the plant Scopolia parviflora, a similar construct using PMT and H6H was used to make transgenic hairy roots.…”
Section: Metabolic Engineering Of Tropane Alkaloidsmentioning
confidence: 99%
“…Overexpression of geraniol 10-hydroxylase (G10H) and a jasmonate-responsive transcript factor (ORCA3) in the HR of Catharanthus roseus improves catharanthine production, another valuable TA [60]. More recently, Kang and coworkers [61] using the same strategy, co-expression of pmt and h6h, obtained transgenic HR lines of Scopolia parviflora. Consequently to the introduction of these key enzyme genes, production of the alkaloids hyoscyamine and scopolamine was enhanced.…”
Section: Overexpression or Co-expression Of Enzymes Involved In The B...mentioning
confidence: 99%